ACHIEVEMENT OF BIOLOGY USING QUESTION STUDENT HAVE ACTIVE LEARNING OBSERVED FROM LEARNING ACTIVITY OF STUDENT’S ON XI IPA GRADE OF SMA NEGERI 1 SUKOHARJO - Rahayu, Eni; Rosyidi, Alvi; Indrowati, Meti (Pendidikan Biologi, 2011)
ABSTRACT ? The purposes of this research were to know: 1)  the influence of learning  strategy  toward achievement   biology of student?s on XI IPA grade of SMA N 1 Sukoharjo  ;  2)  the  influence  of  student?s  learning  activity  toward achievement  biology of student?s  on XI IPA grade of SMA N 1 Sukoharjo ; 3) the interaction between learning  strategy  and student?s learning activity  toward achievement  biology  of student?s  on XI IPA grade  of SMA N 1 Sukoharjo  and;    4) the influence of the combined effects between of  learning strategy  and  student?s learning activity which better  of student?s  on XI IPA grade  of SMA N 1 Sukoharjo  This research was a quasi experiment research with Randomized Control Only Design. Learning strategy and student?s  learning activity were  independent variables and student?s achievement of study biology was the dependent variable. The population of this research was all of student?s on Xl lPA grade of SMAN 1 Sukoharjo. The samples of  this  research were  the student?s of class Xl  IPA 4 as the control class and  student?s of class XI  IPA 3 as  the experimental class. The sample of this research was established by Cluster Random Sampling. The techniques for collecting data were had test, questionnaire, and observation. The data were analyzed by anava two away in different cell and then continued test anova with test LSD to understand treatment influence step. The conclusion of this research were: 1)  the learning strategy had significant influence  toward achievement  biology in cognitive, affective and pshycomotor domain of student?s on XI IPA grade of SMA N 1 Sukoharjo ; 2) the student?s learning activity  had significant influence  toward achievement of biology  in  pshycomotor  but  didn?t  have  significant  influence  in  cognitive and afective domain of  student?s on XI  IPA grade of SMA N 1 Sukoharjo; 3) there wasn?t    interaction between  learning  strategy  and  student?s  learning  activity toward achievement of biologi cognitive, affective and pshycomotor  domain  of student?s on XI IPA grade of SMA N 1 Sukoharjo  and  ;  4)  on the strength of continued test have been  obtained  results that significant  influence the effect of the combination  between  of learning strategy  and learning activity  which the achievemenant biology of higher with the use of active learning Student Question Have observed from the high student?s learning activity in cognitive, affective and psychomotor domain of student?s on XI IPA grade of SMA N 1 Sukoharjo. Keywords : achievement, biology, question student have, active learning, learning Activity